2015
DOI: 10.1016/s0924-9338(15)31346-8
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Polyunsaturated Fatty Acids Can Prevent Relapse in First-episode Schizophrenia: the Results of Offer Trial

Abstract: Introduction: Omega-3 polyunsaturated fatty acids (n3-PUFA) are major constituents of the neural membranes. N-3 PUFA take part in several neuronal mechanisms, including modulation and control of neurobiological processes, such as ion channel and receptor activity, neurotransmitter release, synaptic plasticity, second messenger pathways and neuronal gene expression. Deficiency in n-3 PUFA has been postulated in the etiology of schizophrenia. Intervention trials supplementing n-3 PUFA were conducted to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The data on prevention of progression of the prodrome in schizophrenia are intriguing including on long term follow up of 6.8 years ( Amminger et al, 2015 ). A new study by McGorry et al (2017) did not replicate these finding, but there were many potential explanations including the high use of antidepressants, high rates of non-adherence, and the concomitant use of cognitive-behavioral interventions in both arms, Interestingly, Pawelczyka et al (2015) reported success of omega-3-FA.in decreasing the rate of relapse after a first episode of schizophrenia. Preliminary and open studies in the bipolar spectrum are promising ( Bozzatello et al, 2016 ; Fristad et al, 2015 ; Wozniak et al, 2007 ).…”
Section: Results: Interventions As a Function Of Stage Of Illness Evo...mentioning
confidence: 97%
“…The data on prevention of progression of the prodrome in schizophrenia are intriguing including on long term follow up of 6.8 years ( Amminger et al, 2015 ). A new study by McGorry et al (2017) did not replicate these finding, but there were many potential explanations including the high use of antidepressants, high rates of non-adherence, and the concomitant use of cognitive-behavioral interventions in both arms, Interestingly, Pawelczyka et al (2015) reported success of omega-3-FA.in decreasing the rate of relapse after a first episode of schizophrenia. Preliminary and open studies in the bipolar spectrum are promising ( Bozzatello et al, 2016 ; Fristad et al, 2015 ; Wozniak et al, 2007 ).…”
Section: Results: Interventions As a Function Of Stage Of Illness Evo...mentioning
confidence: 97%